BENEFITING FROM PAST WRONGDOING, HUMAN EMBRYONIC STEM CELL LINES, AND THE FRAGILITY OF THE GERMAN LEGAL POSITION - Takala, Tuija (Bioethics, 2007)
This paper examines the logic and morality of the German Stem Cell Act of 2002. After a brief description of the law's scope and intent, its ethical dimensions are analysed in terms of symbolic threats, indirect consequences, and the encouragement of immorality. The conclusions are twofold. For those who want to accept the law, the arguments for its rationality and morality can be sound. For others, the emphasis on the uniqueness of the German experience, the combination of absolute and qualified value judgments, and the lingering questions of indirect encouragement of immoral activities will probably be too much.